PENGARUH PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP INTENSITAS NYERI MENSTRUASI PADA REMAJA PUTRI - Ika Nur Saputri; Dwi Handayani; Jurpia Yasara (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Menstruation is a natural and natural event, but in reality many women experience menstrual problems, including menstrual pain or dysmenorrhoea. Nonpharmacological menstrual pain management can be done by giving turmeric acid extract. This study aims to determine the effect of giving turmeric acid extract on the intensity of menstrual pain in adolescent girls in State High School 1 Serdang Bedagai Regency in 2020. The research method is quantitative. This type of research is a quasi-experimental design with one-group pretest-posttest design. The study population was 150 class X and XI students of State High School 1 Serdang Bedagai Regency as many as 150 people. The sample selection using purposive sampling as many as 36 people. The results of the study using Wilcoxon sign rank test showed p-value of 0,000 <0.05. The conclusion is there are differences before and after giving turmeric acid drink to the intensity of menstrual pain (dysmenorrhea). It is expected that schools can provide information to students about the use of turmeric acid as a non-pharmacological treatment in reducing menstrual pain.